Onyx removal after embolization of a superior sagittal sinus dural arteriovenous fistula involving scalp artery - Watanabe, Jun (Surg Neurol Int, 2016)
BACKGROUND: Most dural arteriovenous fistula (DAVF) in superior sagittal sinus (SSS) requires multimodal treatment. Onyx embolization is useful for DAVF; however, scalp artery embolization has cast extrusion risk. CASE DESCRIPTION: A 59-year-old male presented with involuntary movements of both legs and progressive dementia. Cerebral angiography demonstrated the DAVF in the SSS fed by bilateral superficial temporal, occipital, and middle meningeal arteries. The posterior SSS was thrombosed, and the main drainers were cortical veins. Combined treatment with transarterial embolization using Onyx and transvenous embolization using coils was performed. Although symptoms were improved, a small DAVF remained. Two months later, Onyx cast extrusion through the scalp was observed, requiring removal and debridement because of infection at the extrusion sites. Surgery for the residual DAVF would be difficult because of scalp condition; therefore, an additional endovascular treatment was conducted, completely occluding DAVF. CONCLUSION: Onyx embolization is useful for DAVF; however, scalp artery embolization has cast extrusion risk. Therefore, scalp infection should be considered because it may preclude additional surgical procedures.